Sistema de informações geográficas para espacialização de dados de pesquisa de satisfação do usuário de empresa de trens urbanos de passageiro - Campos, Guilherme Dutra de (Universidade do Vale do Rio dos Sinos, 2015)
The urban public transportation represents crucial role in mobility of urban centers, affecting the urban dynamics. There has been a major concern to provide better displacement conditions for public transport users. This paper proposes a tool for management actions of user satisfaction and commercial study of Empresa de Trens Urbanos de Porto Alegre. Satisfaction and socioeconomic data were obtained by the report of that research from the satisfaction survey held in 2014 and spatialized through a Geographic Information System (GIS) operated by SPRING 5.3 software. For the preparation of GIS, a basemap was generated, georeferenced and geoprocessing from free images, captured between 2011 and 2015 provided by Google Earth Pro application. The data from satisfaction survey were organized and spatialized. The GIS proved efficient for consult, analysis, comparison and correlation of data, improving decision-making. Provided a spatial vision to the research.
Keywords: SIG; Espacialização; SPRING; Google earth; Transporte público; GIS; Spacialization; Public transportation